The Heirs of Columbus - Vizenor, Gerald Robert, 1934- (Book collections on Project MUSE., 1991)
A novel which turns cultural aggression on its head as the Native American heirs of Christopher Columbus, himself descended from early Mayan explorers, create a fantastic tribal nation.